A Cultura na Política Brasileira - Ferreira, Luzia Aparecida (Políticas Culturais em Revista, 2010)
Este artigo apresenta uma primeira reflexão sobre a elaboração da Nova Lei de Fomento e Incentivo à Cultura, proposta pelo Ministério da Cultura por meio do Projeto de Lei que institui o Programa de Fomento e Incentivo à Cultura – PROFIC, atualmente em trâmite na Câmara dos Deputados e no Senado Federal. Aborda ainda as ações realizadas por parte da sociedade civil no sentido de propor melhorias ao texto da referida Lei, e que acabam se constituindo em mecanismo de poder e barganha com o governo. PALAVRAS CHAVE: Cultura –Brasil. Lei de Incentivo à Cultura. PROFIC. Política-Brasil. The Culture in Brazilian Politics ABSTRACT: This article presents a first reflection on the elaboration of the New Law of Promotion and Incentive to the Culture, which has been proposed by the Ministry of the Culture by means of the Project of Law that institutes the Program of Promotion and Incentive to Culture - PROFIC, currently in process in the House of representatives and the Federal Senate. The article also approaches the actions carried through by part of the civil society in order to consider improvements to the text of the related Law, which end up as becoming a mechanism of power and bargain with the government. KEYWORDS: Culture – Brazil. Law of incentive to the culture. PROFIC. Politics-Brazil.